Shade Avoidance 3 Mediates Crosstalk Between Shade and Nitrogen in Arabidopsis Leaf Development - Yang, Xin-Yue; Zhang, Zhong-Wei; Fu, Yu-Fan; Feng, Ling-Yang; Li, Meng-Xia; Kang, Qi; Wang, Chang-Quan; Yuan, Ming; Chen, Yang-Er; Tao, Qi; Lan, Ting; Tang, Xiao-Yan; et al. (Frontiers in Plant Science, 2022)
After nitrogen treatments, plant leaves become narrower and thicker, and the chlorophyll content increases. However, the molecular mechanisms behind these regulations remain unknown. Here, we found that the changes in leaf width and thickness were largely compromised in the shade avoidance 3 (sav3) mutant. The SAV3 gene encodes an amino-transferase in the auxin biosynthesis pathway. Thus, the crosstalk between shade and nitrogen in Arabidopsis leaf development was investigated. Both hypocotyl elongation and leaf expansion promoted by the shade treatment were reduced by the high-N treatment; high-N-induced leaf narrowing and thickening were reduced by the shade treatment; and all of these developmental changes were largely compromised in the sav3 mutant. Shade treatment promoted SAV3 expression, while high-N treatment repressed SAV3 expression, which then increased or decreased auxin accumulation in cotyledons / leaves, respectively. SAV3 also regulates chlorophyll accumulation and nitrogen assimilation and thus may function as a master switch responsive to multiple environmental stimuli.